Tumor Banks: A Quality Control Scheme Proposal - Craciun, Ligia; Spinette, Selim Alex; Rassy, Marc; Salgado, Roberto; de Wind, Alexandre; Demetter, Pieter; Verset, Laurine; Gomez-Galdon, Maria; Chintinne, Marie; Sirtaine, Nicolas; de St Aubain, Nicolas; Laios, Ioanna; et al. (Frontiers in Medicine, 2019)
Introduction: Tumor banks make a considerable contribution in translational research. Using emerging molecular tests on frozen material facilitates development of new diagnostic and therapeutic strategies, especially in rare cases. However, standard quality control schemes lack in the current literature. Methods: In 2017, we have conducted a robust quality control test on 100 of 15.000 fresh frozen samples collected between 2000 and 2010 at the Jules Bordet Tumor Bank (Brussels). The quality of RNA (RIN), DNA (electrophoretic integrity) and proteins (IHC) were evaluated. A score, ranging from poor (1) to excellent (4), was attributed based on technical analysis. Results: RNA purity was scored 4 in 97% of the cases, 3 in 2% and 2 in 1%. RIN scores were similarly 4 in 89%, 3 in 10% and 2 in 1% of the cases. DNA purity was scored 4 in 94% and 3 in 6%, EI was scored 4 in 100% of the cases. IHC staining on the frozen slide was problematic because of morphology loss after freezing. Nevertheless, after RO, HER2 and ki67 staining, 57 to 83% samples presented a score 4, 15 to 33% samples a score 3 and only 2 to 8% a score 2. Participating to the ISBER Proficiency Testing help us to validate our techniques and the technician’s work. Seven processing schemes were carried out, the scores obtained were very satisfactory (20/27) or satisfactory (7/27). Conclusion: Tumor Banks can be precious for translational research. Nevertheless, firm quality controls should be applied to ensure high quality material delivery. Only then can biobanks contribute to diagnostics, biomarkers discovery and reliable molecular test development.